A cross-national investigation of psychosis-like experiences in five European countries included in the E-CLECTIC study: Psychometric challenges in studying their measurement - Siddi, Sara; Ochoa, Susana; Larøi, Frank; Lincoln, Tania M; Schlier, Björn; Zaytseva, Yuliya; Laloyaux, Julien; Kozáková, Eva; Cella, Matteo; Ntouros, Evangelos; Bozikas, Vasileios; Rocha, Nuno Barbosa; et al. (Psychiatry research, 2024)
BACKGROUND: Psychotic-like experiences (PLEs) are subtle, subclinical perturbations of perceptions and thoughts and are common in the general population. Their characterisation and unidimensionality are still debated. METHODS: This study was conducted by the Electronic-halluCinations-Like Experiences Cross-culTural International Consortium (E-CLECTIC) and aimed at measuring the Community Assessment of Psychic Experiences (CAPE) factorial structure across five European countries (Belgium; Czech Republic, Germany; Greece, and Spain) and testing the adequacy of the unidimensional polytomous Rasch model of the tool via Partial Credit Model (PCM) of the CAPE to detect people with a high risk for developing psychosis. RESULTS: The sample included 1461 participants from the general population. The factorial analysis confirmed the best fit for the bifactor implementation of the three-factor model, including the positive, negative and depressive dimensions and a general factor. Moreover, the unidimensional polytomous Rasch analysis confirmed that CAPE responses reflected one underlying psychosis proneness. CONCLUSIONS: The study proved that the CAPE measures a single latent dimension of psychosis-proneness. The CAPE might help locate and estimate psychosis risk and can be used as a screening tool in primary care settings/education settings.
Keywords: halucinace; lidé; mladiství; Adult; Middle Aged; Cross-Cultural Comparison; Germany; Řecko; faktorová analýza statistická; Greece; psychiatrické posuzovací škály; Female; Evropa; Psychotic Disorders; Adolescent; Humans; Česká republika; Psychometrics; srovnání kultur; Spain; Factor Analysis, Statistical; lidé středního věku; mužské pohlaví; mladý dospělý; Belgium; psychometrie; Czech Republic; ženské pohlaví; Španělsko; Young Adult; Německo; Male; Europe; psychotické poruchy; dospělí; Belgie; Hallucinations; Psychiatric Status Rating Scales